2012
DOI: 10.1016/j.jalz.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Aβ amyloid, cognition, andAPOEgenotype in healthy older adults

Abstract: In APOE ε 4 carriers, there is a moderate negative relationship between cerebral Aβ and episodic memory. This suggests that increased cerebral Aβ may signify the onset of preclinical AD, especially in healthy older adults who are genetically at risk for AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 44 publications
5
38
1
1
Order By: Relevance
“…Our findings align with studies showing verbal memory dysfunction in amyloid positive elderly without dementia (Pike et al, 2007;Rentz et al, 2011;Lim et al, 2014). This relationship between PSM and neocortical amyloid deposition was not changed by controlling for age, gray matter volume, and APOE ε4 carrier status, suggesting a slight divergence from some studies showing a moderating effect of APOE ε4 (Kantarci et al, 2012;Lim et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…Our findings align with studies showing verbal memory dysfunction in amyloid positive elderly without dementia (Pike et al, 2007;Rentz et al, 2011;Lim et al, 2014). This relationship between PSM and neocortical amyloid deposition was not changed by controlling for age, gray matter volume, and APOE ε4 carrier status, suggesting a slight divergence from some studies showing a moderating effect of APOE ε4 (Kantarci et al, 2012;Lim et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…Although in vitro studies suggest that 34 is directly and indirectly related to amyloidosis (Jiang et al, 2008;Liu et al, 2013), clinical evidence for this association in humans remains equivocal. Cross-sectional studies with appropriate sample sizes (e.g., n > 200) report no cognitive impairment in Abþ individuals irrespective of whether they carry 34 (Doraiswamy et al, 2012;Lim et al, 2013aLim et al, , 2013bLim et al, , 2013c. However, potential interactions between Ab and 34 carriage were suggested by observations in 2 different cohorts that associations between Ab levels and memory performance were evident only in 34 carriers (Kantarci et al, 2012;Lim et al, 2013aLim et al, , 2013bLim et al, , 2013c.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies with appropriate sample sizes (e.g., n > 200) report no cognitive impairment in Abþ individuals irrespective of whether they carry 34 (Doraiswamy et al, 2012;Lim et al, 2013aLim et al, , 2013bLim et al, , 2013c. However, potential interactions between Ab and 34 carriage were suggested by observations in 2 different cohorts that associations between Ab levels and memory performance were evident only in 34 carriers (Kantarci et al, 2012;Lim et al, 2013aLim et al, , 2013bLim et al, , 2013c. Initial prospective studies in preclinical AD showed that rates of Ab-related memory decline were not increased when 34 carrier status was added to predictive models (Doraiswamy et al, 2012;Lim et al, 2012;Roe et al, 2013), suggesting that the risk for memory decline and AD posed by 34 carrier status was a consequence of 34 carriage accelerating Ab accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Було обстежено 158 здорових літ-ніх особи з проведенням ПЕТ з PiB (пітсбурзьким лігандом β-амілоїду), генетичного тестування і комплексного нейропсихологічного обстеження. Було показано, що у носіїв АРОЕ4 існує сильний негативний кореляційний взаємозв'язок між ко-роткочасною вербальною пам'яттю і накопичен-ням амілоїдного білка [19]. Крім того, у носіїв АРОЕ4 атрофія гіпокампа з перебігом хвороби роз-вивається швидше.…”
Section: ключові слова: фібриляція передсердь; когнітивні порушення; unclassified